2022
DOI: 10.7150/ntno.58965
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of Raman reporters for the Raman-silent region

Abstract: Rationale: Surface enhanced Raman scattering (SERS) is proving to be a useful tool for biomedical imaging. However, this imaging technique can suffer from poor signal-to-noise ratio, as the complexity of biological tissues can lead to overlapping of Raman bands from tissues and the Raman reporter molecule utilized. Methods: Herein we describe the synthesis of triple bond containing Raman reporters that scatter light in the biological silent window, between 1750 cm -1 and 2750 cm -1 . Results: Our SERS nanoprob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…9CN‐TePY showed a maximum absorption wavelength of 698 nm, which is 28 nm longer than that of 9‐cyano pyronin Y (9CN‐PY), an O‐core derivative (Table 1, Figure 2a, 2b). The SRS spectrum showed a strong single peak at 2217 cm −1 in the cell‐silent region, as observed with other 9‐cyano‐10‐chalcogen‐pyronin derivatives [19] (Table 1, Figure 2c). The relative Raman intensity versus EdU (RIE), [20] which is commonly used as an index of the brightness of Raman probes, was 80, approaching that of other EPR‐SRS dyes available for bioimaging, such as MARS 2238 (RIE=108) [9,12] .…”
Section: Resultssupporting
confidence: 80%
“…9CN‐TePY showed a maximum absorption wavelength of 698 nm, which is 28 nm longer than that of 9‐cyano pyronin Y (9CN‐PY), an O‐core derivative (Table 1, Figure 2a, 2b). The SRS spectrum showed a strong single peak at 2217 cm −1 in the cell‐silent region, as observed with other 9‐cyano‐10‐chalcogen‐pyronin derivatives [19] (Table 1, Figure 2c). The relative Raman intensity versus EdU (RIE), [20] which is commonly used as an index of the brightness of Raman probes, was 80, approaching that of other EPR‐SRS dyes available for bioimaging, such as MARS 2238 (RIE=108) [9,12] .…”
Section: Resultssupporting
confidence: 80%
“…This result is in line with previous reports on the molecule structure‐dependent Raman intensity of different Raman reporters, which further affects the performance of SERS platforms. [ 47,48 ] Besides, we observed a ≈82% decrease of MBA‐peak intensity in RGD–pAS@AuNC group with MBA loaded into mSiO 2 shell when compared to RGD–pAS@AuNC group with MBA directly conjugated to ASNP core (Figure S12c, Supporting Information), suggesting that the EM field enhancement of conjugated MBA molecules in our platform is stronger than that of loaded DOX molecules in the mSiO 2 shell. Consistently, the FDTD simulation results in a literature precedent suggested that the strength of the EM field within the hot spot of an Au‐based nano core‐shell structure is a gradient depending on the distance to the core for core‐shell asymmetric coupling.…”
Section: Resultsmentioning
confidence: 89%
“…On a different note, Plakas et al have modified pyrylium dyes by incorporating alkynes in their chemical structure and altering their functionality in order to produce Raman reporters for the cell – silent region. 85 The pyrylium-and xanthylium dyes were later adsorbed on gold nanoparticles and identified to be potential candidates for SERS applications at 638 and 785 nm excitation wavelength.…”
Section: Molecular Labelling At the Cell – Silent Raman Window And Ap...mentioning
confidence: 99%